Contextualising the impact of ancient Greek and Roman superstition on public life (2018)
Consensus on the meaning of superstition remains elusive. Even when dangers allegedly exist, the controversy over the subject has engendered caution against sounding polemical or judgemental by labelling any belief as superstitious. This paper considers undue restraints as insidious and identifies when superstition is inimical to the society. The study indicates various degrees of damage caused by seemingly innocuous traditional/religious beliefs in ancient Greek and Roman climes. Max Weber's social action theory has been adopted as theoretical framework to do a library study of works of Theophrastus, Plutarch, Livy and Petronius. These ancient sources offer the platform for examining superstition as clinging to certain behavioural patterns even when no relationship exists between causes and effects. Attention is paid to how superstition surreptitiously becomes hostile to private and community interests. The paper argues that superstition emerges when customs, routines or habits that lack empirical basis take on harmful legislative powers on people and diminish the quality of their lives. The submission is that admission of past and present errors in perception of esoteric experiences should be unambiguous if the grip of superstition would be eliminated. Viewed as a clog in the wheel of meaningful social development, superstition should be stripped of its overbearing garb of subjective thinking that riddles life with morbid fear and places unfair burden of guilt on the human society.